Pengaruh Konfigurasi Tabung Kompresor Terhadap Unjuk Kerja Pompa Hidram - Fane, Didin S.; Sutanto, Rudy; Mara, Made (Universitas Mataram, 2012)
AbstractA hydraulic ram pump is a cyclic water pump powered by hydropower. It functions as a hydraulic transformer that takes in water at one pressure and flow rate, and outputs water at a higher hydraulic head and lower flow rate. Hydraulic ram pump uses the water hammer effect to develop pressure that allows a portion of the input water that powers the pump to be lifted to a point higher than where the water originally started. The hydraulic ram pump is used in remote areas, where there is both a source of low-head hydropower and a need for pumping water to a destination higher in elevation than the source.In this research using tube compressor with 3-inch tube diameter and height 25 centimeters. Level of water used is at position 5 meters with 8 meters height of calculate the output discharge. The observed parameters are input pressure, output pressure, the tube compressors pressure; valves waste pressure, water discharge input, output water flow and pump efficiency.The result showed that hydram pump ILK position, with parallel compressor tube configuration have better performance than the configuration of compressor tube series. Which the maximum head 22 meters is achieved. And discharge result at the height calculated (8 meters) of 0.0453 liters / sec and 3.278% efficiency.